MIX OF FISCAL POLICY AND MONETARY POLICY IN HANDLING COVID19 - Wicaksana, Kuscahya (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The aim of this research is to analyze the fiscal policy mix through the allocation of funds in the APBN and monetary policy through various relaxations of banking regulations. This research is qualitative in nature and the data source taken is secondary data. Data collection techniques, namely data reduction, data display and drawing conclusions. The Covid-19 pandemic has had an unexpected impact on the world economy. Indonesia is also not free from its impact, state revenues which come partly from community activities and activities have decreased significantly along with restrictions on community activities. In this situation, the government is supported by economic theory that supports government intervention to restore the national economy implementing a mix of fiscal policies through the allocation of funds in the APBN and monetary policy through various relaxations of banking regulations. The policy mix which was implemented consistently and closely monitored resulted in very satisfactory improvements in economic and social conditions.